Representación burlesca de los personajes en El pánico de Rafael Spregelburd: la incidencia de las réplicas en la emergencia del ethos autoral - Zucchi, Mariano Nicolás (2022)
This article analyses the footing adopted by the authorial ethos (Amossy 2009) in El pánico ([2004] 2016), by Rafael Spregelburd. In particular, we will examine the specific way in which the theatrical dialogue generates a burlesque representation of the main characters. This image will allow us to deduce that the playwright emerges as someone who mocks them. Regarding the theoretical framework of this study, we used the dialogic approach to argumentation and polyphony (Caldiz 2019, García Negroni 2009a, 2016a, 2016b, 2018a, 2018b, 2018c, 2019, García Negroni y Libenson 2016, 2018, 2019a, 2019b), a non-referential theory of linguistic meaning.